A preliminary analyze of cranial variations in three Amphisbaenia species - Hohl, Leandro (2023)
Amphisbaenia is a fossorial group of Reptiles. They display morphological adaptations to burrowing, namelly, a cylindrical and elongated body, a tendency to lack legs, and a strongly ossified and compacted skull. Regarding the skull four morphotypes can be assumed: roundheaded, spade-headed, keel-headed, and shovel -headed, beeing the snout region the main cranial variation. The intermediate region of the skull and the occipital zone are more constant in the different species of the group. However, it is worth mentioning that these skull regions are particularlly related to many aspects of their life, such as excavation activity and related bite force, for example. We hypothesize that there are significant variations in these skull regions between different species and that such variations may be related to their lifestyles. The main objective of our research was to analyze, in a preliminary way, cranial variations between three species of Amphisbaenia nameli, Amphisbaena darwinii, Blanus cinereus (both with a rounded skull), and Leposternon microcephalum (with a snout-headed skull). For this, computerized microtomography of four adult specimens of each species were analyzed using 3D Geometric Morphometrics, based on 22 landmarks describing the intermediate and occipital skull regions. Associated Principal Component Analyzes showed a clear difference between the three species studied.